El conocimiento profesional de los (as) profesores (as) de ciencias: algunos aspectos centrales en el desarrollo de la línea de investigación - Martínez Rivera, Carmen Alicia (Revista Científica, 2011)
A revision appears from which it is possible to indicate to the Professional Knowledge of (ace) the Profesores (as) de Cadencies, like a problem of great relevance in the Didactics of Sciences. Excellent antecedents in the sprouting of this line of investigation are approached.